2004
DOI: 10.1136/gut.2003.027136
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor expression on T lymphocytes modulates chronic intestinal inflammation in mice

Abstract: Background: Leptin regulates appetite through the long isoform of its receptor in the hypothalamus. Although leptin regulates immune responses, it is still unknown whether a direct effect of leptin on lymphocytes is required. Aims: To clarify whether expression of leptin receptors on T lymphocytes modulates intestinal inflammation in mice. Methods: The model of colitis induced by transfer of CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 28 publications
6
80
1
3
Order By: Relevance
“…The leptin receptor (Ob-R), a member of class I cytokine receptors, is encoded by the diabetes (db) gene and is expressed in peripheral B cells, T cells, NK cells, and monocyte macrophages (2)(3)(4)(5)(6). Leptin has been increasingly recognized as a cytokine-like hormone with pleiotropic actions in modulating immune responses (7).…”
mentioning
confidence: 99%
“…The leptin receptor (Ob-R), a member of class I cytokine receptors, is encoded by the diabetes (db) gene and is expressed in peripheral B cells, T cells, NK cells, and monocyte macrophages (2)(3)(4)(5)(6). Leptin has been increasingly recognized as a cytokine-like hormone with pleiotropic actions in modulating immune responses (7).…”
mentioning
confidence: 99%
“…A histological observation of the colon revealed marked inflammation in mice injected with wild-type cells, whereas no inflammation was observed in mice receiving db/db cells. 44,89 Serum leptin levels are not altered in human inflammatory bowel diseases, although they might increase during the acute stages of ulcerative colitis. Furthermore, leptin mRNA is upregulated in mesenteric adipose tissue of these patients.…”
Section: Leptin Connective Tissue Diseases and Organ-specific Autoimmentioning
confidence: 99%
“…Despite the name 'eosinophilic', EGCs may have different staining affinities, basophilic or eosinophilic, depending on the species considered and the conditions of fixation (Rocha & Chiarini-Garcia 2007). The involvement of leptin in inflammation is well-established in birds and mammals (Lõhmus et al 2004;Matarese et al 2005); in particular, it has been demonstrated that, in the mammalian intestine, lymphocytes release leptin at the inflammation site (Siegmund et al 2004;Fantuzzi et al 2005). Our data therefore suggest that leptin can be involved in immune and inflammatory responses in teleosts, in addition to its better-known role as a regulator of energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%